2005
DOI: 10.1542/peds.2005-0999
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Pregnancy: Current Trends and Issues

Abstract: ABSTRACT. The prevention of unintended adolescent pregnancy is an important goal of the American Academy of Pediatrics and our society. Although adolescent pregnancy and birth rates have been steadily decreasing, many adolescents still become pregnant. Since the last statement on adolescent pregnancy was issued by the Academy in 1998, efforts to prevent adolescent pregnancy have increased, and new observations, technologies, and prevention effectiveness data have emerged. The purpose of this clinical report is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
198
2
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(215 citation statements)
references
References 47 publications
8
198
2
7
Order By: Relevance
“…On the marital status of adolescent girls, the results showed that 49.31% live in free union, which is not surprising, because as evidenced by the study of Gomez and Montoya (14), conducted in a population in Medellin, Colombia , living with the couple has been associated with increased desire to have children, as well as increased risk (16.47 times) to get pregnant; this situation can be explained by dysfunction of the primary household and desire of the adolescent to form a new home (15).…”
Section: Population Characteristicsmentioning
confidence: 79%
See 1 more Smart Citation
“…On the marital status of adolescent girls, the results showed that 49.31% live in free union, which is not surprising, because as evidenced by the study of Gomez and Montoya (14), conducted in a population in Medellin, Colombia , living with the couple has been associated with increased desire to have children, as well as increased risk (16.47 times) to get pregnant; this situation can be explained by dysfunction of the primary household and desire of the adolescent to form a new home (15).…”
Section: Population Characteristicsmentioning
confidence: 79%
“…Have proposed several reasons why adolescents are at risk for pregnancy at a very young age, including early pubertal development, early initiation of sex, ignorance in the use of contraception, sex does not consensual, personal history of sexual abuse in childhood and other sociodemographic reasons, such as low education, poor school performance, family dysfunction, among others (15).…”
Section: General Featuresmentioning
confidence: 99%
“…Abortus, erken doğum, hipertansiyon, anemi, yetersiz antenatal bakım, düşük doğum ağırlıklı bebekler, konjenital anomaliler, artmış sezeryan oranı, bulaşıcı hastalıklar gibi insan sağlığını tehdit eden durumların arttığı bildirilmiştir (15)(16)(17)(18). Olgumuz erken yaş hamilelik ve yetersiz antenatal bakım yüzünden sezeryan ameliyatı olmak zorunda kaldığı gibi, prematüre ve düşük doğum ağırlıklı bir bebeğe sahip olmuştur.…”
Section: Sonuçunclassified
“…67 Nationally, approximately 50% of adolescents have engaged in sexual intercourse by age 17, however it is not clear to what extent this is true for extremely obese youth, as weight-related stigma may affect rates of sexual activity. 68 Though the weight loss associated with gastric bypass has been shown to reduce weight-related complications of subsequent pregnancies in adults, it is important to counsel adolescent females to avoid pregnancy during the period of rapid weight loss and up to 12-18 months after surgery. 69 Further, adolescent pregnancy in general is associated with a higher incidence of complications, such as prematurity and low birth weight, though outcomes of pregnancy in adolescent females after bariatric surgery have not yet been systematically studied.…”
Section: Nutritional Risks Of Weight Loss Surgerymentioning
confidence: 99%
“…69 Further, adolescent pregnancy in general is associated with a higher incidence of complications, such as prematurity and low birth weight, though outcomes of pregnancy in adolescent females after bariatric surgery have not yet been systematically studied. 68 Higher rates of specific nutritional deficiencies after bariatric surgery can place the mother and infant at greater risk. In particular, deficiencies in iron, folate, vitamin B12, calcium and vitamin D can result in poor fetal growth or even malformation.…”
Section: Nutritional Risks Of Weight Loss Surgerymentioning
confidence: 99%